Code switching in telephone conversation / Alif Zulkefle - Zulkefle, Alif (2011)
This qualitative study investigated code-switching in telephone conversation, with a focus on gender differences. Conversations were taken as samples from a local radio call-in program. The telephone conversations were first listened to and then categorized according to the gender. Once filtered to different genders, the conversations were analyzed and the code-switches were categorized according to their functions. The sample were recorded and downloaded from the radio online archive, which are then transcribed and analyzed using Gumperz Semantic Model (1982). Six functions of codeswitching, which are personalization or objectivisation, quotation, message qualification, situational code-switching, interjection and reiteration, noted from the telephone conversations. The function of code-switch used most by both the male and female subjects is personalization or objectivisation. Study also showed that the females codeswitch more than the male in the telephone conversations of this nature. This study also provides pedagogical implications and suggestions for future research.